Political economy of foreign direct investment : a framework for analysing investment laws and regulations in developing countries. - Kofele-Kale, Ndiva (1992)
Examines the relationship between foreign direct investment and host country investment laws and policies, utilizing transnational quantitative data for Cameroon, Cote d'Ivoire and Kenya. Presents a conceptual framework to test the hypothesis that the flow of FDI to developing countries increases in response to the generosity of the host country's investment policies.